The Prospects of the Arts Promotion in the Context of Limitations and Consequences of Self-Isolation - Kalashnyk, Mariya P.; Novikov, Iurii M.; Varakuta, Maryna I.; Genkin, Anton O.; Kupina, Daryna D. (International Journal of Criminology and Sociology, 2021)
The rapid development of events related to the coronavirus pandemic has led to a crisis not only in the financial sector, but also in the field of art and culture. According to various international organisations, losses for the sphere of culture and art amount to tens of billions of dollars due to the forced quarantine. Museums and philharmonic societies closed and hundreds of concerts were cancelled. The artists faced a problem – to find and involve an audience in their work, contacting them only via the Internet. Many cultural institutions were able to transfer their resources to the digital sphere quite quickly (using digital resources). The relevance of the study is due to the fact that the crisis brought about by the coronavirus pandemic forced representatives of the cultural and artistic sector to look for new forms of functioning and communication with the audience. In this regard, this paper is aimed at identifying the consequences of forced self-isolation on the development of art and creativity of specific cultural figures. The leading method for the study of this subject is the method of analysis, which makes it possible to comprehensively assess the following areas: the activities of Ukrainian and world museums, theatres and philharmonic societies during quarantine, their methods of maintaining communication with the audience; the theme of the work of artists and illustrators during the pandemic, their ways to share their work without the possibility of organising exhibitions and art residences; work of musicians in isolation. One of the main conclusions in this situation was the need to use digital technologies as a platform to demonstrate the results of the creative process. Another important issue remains the search for new funding opportunities for the cultural sector during a crisis, since dependence on the state budget and donors can be unstable.